Changes in non-high-density lipoprotein to high-density lipoprotein ratio (NHHR) and cardiovascular disease: insights from CHARLS - Bingxue Wang; LiYing Li; Ying Tang; Ting Lin; Jing Wu; Guoqi Wang; Xingwu Ran (Lipids in Health and Disease)
Abstract Background The established association between the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and cardiovascular disease (CVD) risk has been well-documented. Nevertheless, the relationship between changes in NHHR and CVD events remains to be elucidated. The present study aims to clarify the correlation between NHHR change patterns and the incidence of CVD across a broad population. Methods The current study recruited participants from the China Health and Retirement Longitudinal Study (CHARLS). The NHHR index was calculated using the formula: NHHR = (TC-HDL-c)/HDL-c. Temporal changes in NHHR were assessed with latent profile analysis, and cumulative NHHR was also evaluated. Multivariable Cox proportional hazards regression models and multivariate-adjusted restricted cubic spline (RCS) analyses were employed to examine the association between the NHHR index and incident CVD. Results A total of 4,629 individuals were recruited for the study. The average age of the participants was 57.47 years, with 53.7% being female. Over the follow-up period, 879 cases of CVD were documented. Compared to participants in the lowest tertile, those in the highest tertile for both baseline NHHR and cumulative NHHR exhibited a significantly increased risk of CVD, with adjusted hazard ratios (HRs) of 1.43 (95% confidence interval [CI]: 1.21–1.70) and 1.45 (95% CI: 1.23–1.72), respectively. Participants classified in Class 2 demonstrated a 27% higher risk of CVD, while those in Class 3 showed a 41% greater risk compared to the Class 1 group. Further analysis revealed that this relationship was linear. Stratified analyses corroborated the primary findings. Conclusion Baseline NHHR, cumulative NHHR, and changes in NHHR are significantly associated with an increased risk of CVD among individuals aged 45 years and older, thereby confirming their potential as valuable tools for risk stratification in CVD.